IEEE INFOCOM 2020 - IEEE Conference on Computer Communications 2020
DOI: 10.1109/infocom41043.2020.9155401
|View full text |Cite
|
Sign up to set email alerts
|

PASID: Exploiting Indoor mmWave Deployments for Passive Intrusion Detection

Abstract: As 5G deployments start to roll-out, indoor solutions are increasingly pressed towards delivering a similar user experience. Wi-Fi is the predominant technology of choice indoors and major vendors started addressing this need by incorporating the mmWave band to their products. In the near future, mmWave devices are expected to become pervasive, opening up new business opportunities to exploit their unique properties.In this paper, we present a novel PASsive Intrusion Detection system, namely PASID, leveraging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…More recently, CNNs have inspired several works addressing the problem of indoor localization. [44] demonstrates a low-cost intrusion detection mechanism built on COTS hardware able to detect intruders up to 99% accuracy at 2% additional energy cost. Along these lines, [45]- [47] tackle the localization accuracy in harsh environments, showing that CNNs are able to mitigate NLoS effects and obtain sub-meter accuracy with Ultra Wide Band (UWB) signals.…”
Section: Related Workmentioning
confidence: 99%
“…More recently, CNNs have inspired several works addressing the problem of indoor localization. [44] demonstrates a low-cost intrusion detection mechanism built on COTS hardware able to detect intruders up to 99% accuracy at 2% additional energy cost. Along these lines, [45]- [47] tackle the localization accuracy in harsh environments, showing that CNNs are able to mitigate NLoS effects and obtain sub-meter accuracy with Ultra Wide Band (UWB) signals.…”
Section: Related Workmentioning
confidence: 99%
“…The probing and communication phases necessitate highly directive codebooks in order to scan the 3D space with a fine spatial resolution [19], [20]. To this end, we partition the total scanning angle into L angular sectors [φ l , φ l+1 ] with φ l+1 − Algorithm 2 MARISA -Communication phase…”
Section: B Codebook Designmentioning
confidence: 99%
“…But in this test case, it is identified that it is GPS spoofing. In this work, the structure of a passive IDS is used (DEVOTI et al, 2020;TIAN et al, 2018). When it identifies that the vulnerability is not a false positive, it issues an alarm to the administrator (decision-making module) to prevent the invasion from continuing.…”
Section: :32:52mentioning
confidence: 99%